A Case History of Shallow Aquifer Contamination Studies (Journal of Science and Technology, 2016)
Degradation of the quality of groundwater resources as a result of contamination from hazardous industrial landfill sites, mining operations, agricultural chemicals and pesticides and solid and liquid waste constitutes one of the major environmental concerns in both developed and developing countries today. The paper presents a case history of an integrated environmental geotechnological study involving the application of geoelectric sounding techniques, drilling and water quality monitoring in the assessment of the extent of groundwater contamination in the vicinity of an industrial hazardous waste landfill site in Tema, Ghana. The findings of the study confirmed the conclusions of other investigators that geoelectric sounding techniques may not yield conclusive results in groundwater contamination studies in situations of complex geology.